ANALISA EFEKTIFITAS PEMBELAJARAN DARING SAAT PANDEMI COVID-19 PADA FAKULTAS ILMU KOMPUTER UNIVERSITAS LANCANG KUNING - Djusar, Syahtriatna; Sadar, Muhammad; Asril, Elvira (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2021)
The Covid-19 pandemic has changed the learning model of higher education in Indonesia from face-to-face meetings to online learning. This study aims to analyze the effectiveness of online learning during the Covid-19 Pandemic at the Faculty of Computer Science, Lancang Kuning University (Fasilkom Unilak). The effectiveness measured is related to the application used, the content in the learning, the device used, the time used, the cost used, the interaction between students and lecturers. The form of the variable is a single variable. Using a questionnaire with 26 questions. The object of this research is 63 students of class 2018 and 2019 who are active and take part in online learning. After measuring, all the variables used were declared valid and reliable. Of the 6 indicators of effectiveness measured using the percentage formula, the results obtained for all indicators are said to be effective. The determined effective limit is 50%. The results of the indicator measurements, all of them have a value of more than 50%. Based on the measurement results, it is stated that online learning during the covid-19 pandemic at the Faculty of Computer Science, Lancang Kuning University is said to be effective with an average measurement result of above 50%.